2013
DOI: 10.1111/eva.12083
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide tolerance in amphibians: induced tolerance in susceptible populations, constitutive tolerance in tolerant populations

Abstract: The role of plasticity in shaping adaptations is important to understanding the expression of traits within individuals and the evolution of populations. With increasing human impacts on the environment, one challenge is to consider how plasticity shapes responses to anthropogenic stressors such as contaminants. To our knowledge, only one study (using mosquitoes) has considered the possibility of induced insecticide tolerance. Using populations of wood frogs (Lithobates sylvaticus) located close to and far fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 44 publications
(78 reference statements)
6
113
1
Order By: Relevance
“…Also, some level of pesticide tolerance for amphibians from agricultural breeding pond populations was detected (Hua, Morehouse & Relyea, 2013; Hua et al, 2015). Yet such findings should not be generalized, since tested taxa and pesticides were limited, and pesticides still may cause lethal or sublethal effects on amphibians, depending on the path of exposure, exposure level and amphibian life stage.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some level of pesticide tolerance for amphibians from agricultural breeding pond populations was detected (Hua, Morehouse & Relyea, 2013; Hua et al, 2015). Yet such findings should not be generalized, since tested taxa and pesticides were limited, and pesticides still may cause lethal or sublethal effects on amphibians, depending on the path of exposure, exposure level and amphibian life stage.…”
Section: Discussionmentioning
confidence: 99%
“…By quantifying both evolved and inducible (i.e . plastic) tolerances of wood frog populations varying in their distance from agriculture to an insecticide, Hua and colleagues found that evolved tolerance to a potentially lethal exposure of insecticide decreased with distance from agriculture 76, 79 . In contrast, the degree of plastic tolerance induced from an initial sublethal exposure increased with distance from agriculture 76 .…”
Section: Existing Plasticity Evolutionary Potential and The Role Ofmentioning
confidence: 99%
“…Our experimental units were 100-mL, glass Petri dishes filled with either 70 mL of water (control) or 70 mL of the lethal carbaryl, malathion, cypermethrin, imidacloprid, and thiamethoxam solutions. Because our objective for the TTD assays was to cause moderate mortality over time (Newman, 2010), we chose different lethal concentrations for each pesticide based on past studies (Hua et al, 2013b) and pilot data; the concentrations were as follows: carbaryl ¼ 25 mg/L, malathion ¼ 9.5 mg/L, cypermethrin ¼ 30 mg/L, permethrin ¼ 40 mg/L, imidacloprid ¼ 95 mg/L, and thiamethoxam ¼ 38 mg/L. The expectation is that TTD assays, which use relatively high concentrations to assess the relative sensitivities to different insecticides, provide information regarding sublethal effects (Newman, 2010).…”
Section: Experimental Designmentioning
confidence: 99%